Amiloride-sensitive Na channels from the apical membrane of the rat cortical collecting tubule. - Palmer, L G (1986)
Currents through individual Na channels in the apical membrane of the rat cortical collecting tubule were resolved by using the patch-clamp technique. In cell-attached patches, the channels had a conductance of 5 pS with 140 mM NaCl in the pipet. The conductance was a saturable function of external Na, with a maximal value of about 8 pS and a half saturation at about 75 mM Na. In excised inside-out patches, the selectivity of the channels for Na over K was estimated from reversal potentials to be at least 10:1. The channels underwent spontaneous transitions between open and closed states. Both states had mean lifetimes of 3-4 sec. Amiloride (0.5 microM) added to the pipet induced more frequent closures and openings of the channels and a reduction in the mean open time. These channels are presumed to mediate Na reabsorption by this nephron segment in vivo.